Nutritional balance of the "average" Bunaji cow - Milligan, K.; Kaufmann, Ralph R. von (International Livestock Centre for Africa, 1979)
Presents data on the nutritional balance of cows at Kurmin Biri in Nigeria under traditional "settled" Fulani pastoralism, with particular reference to nutrient requirements, dry matter appetite, contents of available feed sources, and supplement requirements.